Radial Evolution of Ultrarelativistic Electrons During Enhancement Events - Stepanova, M; Pinto-Abarzua, V; Zenteno-Quinteros, B (IOP Publishing Ltd, 2025)
In this work, we used a dataset of 60 relativistic electron enhancement events measured at geostationary orbit (GEO) to study the correlation between the >2 MeV and >4 MeV electron fluxes. We then use the fluxes at GEO to compare against in-situ measurements from the Van Allen Probes mission and study the radial response of outer belt fluxes and the correlation between the fluxes at GEO and those closer to the Earth. The enhancement events occurred between 1 October 2012 and 31 December 2017 and were identified using Geostationary Operational Environmental Satellite (GOES) 15 >2 MeV fluxes at GEO. We compare with fluxes measured by the Van Allen probes Energetic Particle, Composition and Thermal Plasma Suite Relativistic Electron-Proton Telescope (ECT-REPT) between 2.5 < L < 6.0 at E = 2.1 MeV and E = 4.2 MeV. We found that the response of the radiation belts during enhancement events is very homogeneous for L > 4.0 and extremely similar for L > 5.0. Post-enhancement maximum fluxes show a remarkable correlation for all L > 4.0 at both the 2.1 MeV and 4.2 MeV energies, indicating that modeling or forecasting efforts of the outer radiation belt using data from geostationary orbit are justified.